Implementasi Tata Tertib Pesantren Dalam Membangun Kedisiplinan Santri Di Pondok Pesantren Lubabuth Tholibin Desa Sangubanyu Kecamatan Buluspesantren Kabupaten Kebumen Tahun Ajaran 2023/2024 - Khasanah, Siti Khanifatun; Murtajib, Ahmad (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Islamic Boarding School are non-formal educational institutions that have the aim of forming students who behave in accordance with applicable value and norm. This research is a qualitative research with a descriptive research design. The aim of this research is: (1) To find out the application of rules and regulations at the Lubabuth Tholibin Islamic Boarding School Sangubanyu village; (2) to find out the condition of santri discipline after impelementing the rules at the Lubabuth Tholib Islamic Boarding School Sangubanyu village. Data collection techniques used are interviews, observation, and documentation. The data analysis techniques used are data collection, data condensation, data presentation and drawing conclusion. Based on the research, it can be concluded that implementation of rules and regulations in building student discipline at the Lubabuth Tholibin Boarding Scholl with several implementations, among others: introduce rules especially for new students, set an example in obeying the rules, providing transportation as a means of scholl pick-up and drop-off, entering into an MOU with the school, give punishment to student who violate the rules. The disciplinary conditions of female students after implementing the following rules and regulations: growing students awareness of time discipline, high enthusiasm for reciting the koran, islamic boarding scholl students rarely hang out during school hours and islamic boarding students do not borrow vehicles from the local community